2022
DOI: 10.1177/10760296221146183
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Hematologic Inflammatory Markers in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: The aggregate index of systemic inflammation (AISI), systemic inflammation response index (SIRI), and neutrophil-to-lymphocyte*platelet ratio (NLRP) are novel indices that simultaneously reflect the inflammatory and immune status. However, the role of these indices in acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI) remains unclear. We aimed to elucidate the predictive value of AISI, SIRI, and NLRP in patients with ACS undergoing PCI. A total of 1558 patients with ACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The study points out that elevated levels of inflammatory markers are commonly found in older adults, and inflammation may be a primary factor leading to frailty (40, 41). The association between changes in the immune system and frailty involves multiple pathways, with neutrophils being a crucial biomarker for innate immunity, platelets potentially contributing to immune function, and lymphocytes providing rich information about adaptive immunity (42,43). SII and SIRI have demonstrated exceptional validity as emerging biomarkers in various diseases (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study points out that elevated levels of inflammatory markers are commonly found in older adults, and inflammation may be a primary factor leading to frailty (40, 41). The association between changes in the immune system and frailty involves multiple pathways, with neutrophils being a crucial biomarker for innate immunity, platelets potentially contributing to immune function, and lymphocytes providing rich information about adaptive immunity (42,43). SII and SIRI have demonstrated exceptional validity as emerging biomarkers in various diseases (44).…”
Section: Discussionmentioning
confidence: 99%
“…The association between changes in the immune system and frailty involves multiple pathways, with neutrophils being a crucial biomarker for innate immunity, platelets potentially contributing to immune function, and lymphocytes providing rich information about adaptive immunity ( 42 , 43 ). SII and SIRI have demonstrated exceptional validity as emerging biomarkers in various diseases ( 44 ). SII’s predictive ability for major cardiovascular events in coronary heart disease patients undergoing coronary intervention surpasses traditional risk factors ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIRI combines neutrophils, monocytes, and lymphocytes to represent the balance between inflammation activators and regulators in the host. Composite indicators are more stable than single indicators, and high SIRI status reflects mediated by monocytes and neutrophils and a weak anti-inflammatory response mediated by lymphocyte ( 59 ). To the best of our knowledge, this is the first study to report the role of SIRI in hypertension in PLWH and the correlations between SIRI and T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Non-ST segment elevated myocardial infarction requires complex pathophysiological mechanisms of systemic/local inflammatory, immunological, and thrombotic systems, which are influential in the formation and progression of atherosclerosis. Among these factors, the study of inflammation and inflammation-based markers has become a prominent topic in recent years [ 12 ].…”
Section: Introductionmentioning
confidence: 99%